Ethical consumption among Cape Town students: a qualitative study - McMahon, Molly (Department of Environmental and Geographical Science, 2016)
Much of current research on ethical consumption biases the North - South relationship of Northern consumers being considered ethical based on their purchasing of items from Southern producers. This establishes the dominant perspective of ethics needing to be expressed toward the distant other and to be based in a specific object, often typified by Fair Trade. These conditions of ethics have led to the assumption that Southern consumers lack ethics in their consumption. Thus this research seeks to expand the current understanding of ethical consumption to include ethics at home and ethics of care, as well as expand the demographic of ethical consumption studies to include Southern consumers. The aim of this research is to add to the developing understanding of Southern ethical consumption through the exploration of ethics in grocery shopping among students. Students from various universities in the Cape Town area were observed while grocery shopping and interviewed about their shopping habits and their thoughts on ethics and values, particularly in terms of consumption and food. Twenty - eight students were interviewed, and of those, 23 were also observed shopping. At the conclusion of this study, it is evident that students, as Southern consumers, do express ethical consideration in their consumption habits. This is based on both perspectives of ethical goods and ethical practices. However, they are more apt to act on the ethics of care at home than on the ethics of care at a distance. The strongest trends among students are thrift, care at home and care for self, as well as a significant draw toward s shopping local and supporting local producers based in their communities and nationally. The implications of this research are that it adds to the literature through its theorization within the Global South, its focus on ethical consumption as a practice instead of solely object - based and the discussion of students as a research demographic. Overall, this study demonstrates how Southern consumers do express ethics in their shopping choices particularly through care at home.